El mirador de Deleuze como detonante para repensar los estudios sobre el arte de la animación - Valle Gómez, Daniel (Eikón / Imago, 2024)
The present text parts from the actual state of the reflection about animation art and borderings to propose a previous thinking to the visual, a view to take a look and think the artistic animated object before we will be able to go deep into its stratigraphic complexity. This overlook are the images offered by the French philosopher Gilles Deleuze, who breaks through the historic and aesthetics images of the cinema and the constituent components such as the animated art as the thinking able to think it in all its whole magnitude.The crux of the matter resides in the lenticularity of these images which traze the lines of the intellibility needed to articulate the relations that go from the perception and the sensorial system to the subjective renewal. This makes that the expression of the work comes back again and again in a different way. And in the middle of everything, the almost innocent notion of the movement remains so that in the cinematographic arts and from the animated image what we found is a pure change, progression, experience, movement, that is, images in motion.